2020
DOI: 10.3390/cancers12102779
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index Less Than 92 Is a Predictor for Late Postpancreatectomy Hemorrhage Following Pancreatoduodenectomy: A Retrospective Cohort Study

Abstract: Postpancreatectomy hemorrhage (PPH) is the most lethal complication of pancreatoduodenectomy (PD). The main risk factor for PPH is the development of a postoperative pancreatic fistula (POPF). Recent evidence shows that the geriatric nutritional risk index (GNRI) may be predictive indicator for POPF. In this study, we aimed to evaluate whether GNRI is a reliable predictive marker for PPH following PD. The present study retrospectively evaluated 121 patients treated with PD at Ageo Central General Hospital in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, no robust evidence has been established to support surgical techniques. In contrast, a number of POPF risk factors have been suggested, such as a soft pancreas, obesity, diabetes mellitus, a lower geriatric nutritional risk index (GNRI), lower albumin levels, blood loss, and an extended operation time [29][30][31]. Notably, a meta-analysis revealed that a soft pancreas, a higher BMI, blood transfusion, blood loss, and the operative time were major predictors of POPF [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, no robust evidence has been established to support surgical techniques. In contrast, a number of POPF risk factors have been suggested, such as a soft pancreas, obesity, diabetes mellitus, a lower geriatric nutritional risk index (GNRI), lower albumin levels, blood loss, and an extended operation time [29][30][31]. Notably, a meta-analysis revealed that a soft pancreas, a higher BMI, blood transfusion, blood loss, and the operative time were major predictors of POPF [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, a definitive risk factor for POPF has not yet been established. For such occasions, several POPF predictive scores, including inflammatory and/or nutritional status, have been developed, such as the GNRI [ 4 , 5 ], controlling nutritional status score [ 20 ], and prognostic nutritional index [ 22 ] to detect POPF at an earlier phase and with more precision. In addition, those scores using inflammatory or nutritional status, such as GNRI [ 23 ], the platelet-to-lymphocyte ratio [ 24 ], and neutrophil-to-lymphocyte ratio (NLR) [ 25 , 26 ], have been designed as prognostic factors in several types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent evidence has shown that POPF unfavorably affects the prognosis in patients with pancreatic cancer [ 3 ]. We previously showed that the geriatric nutritional risk index (GNRI) could predict POCs among patients who underwent pancreatic resection for periampullary diseases [ 4 , 5 , 6 , 7 ]. Instead of GNRI as a nutritional parameter, we explored another novel indicator for the risk of POPF following PD.…”
Section: Introductionmentioning
confidence: 99%
“…This index can predict the complications induced by malnutrition as well (Cereda et al., 2009 ). Predictions of some diseases incidence and prognosis have been made through GNRI in earlier investigations, including postoperative survival rate of esophageal cancer (Kubo et al., 2019 ), postoperative complications of gastric cancer (Kushiyama et al., 2018 ), postoperative bleeding of the pancreas (Funamizu et al., 2020 ), mortality of heart failure (Li et al., 2021 ), the prognosis of coronavirus disease(COVID‐19) (Lidoriki et al., 2020 ; Recinella et al., 2020 ), and poststroke cognitive impairment (Lee et al., 2021 ). Besides, studies have also found that malnutrition can lead to complications such as decreased immunity and infection (Keusch, 2003 ).…”
Section: Introductionmentioning
confidence: 99%